Polyoxometalates Surrounded by Organic Cations or Immobilized on Functionalized Merrifield Resin as Catalysts for Oxidation of β-Myrcene and β-Caryophyllene - Ali Al Hadi Haidar; Pascal Guillo; Dominique Agustin (Applied Sciences, 2025)
Polyoxometalates (POMs) surrounded by organic cations and related systems composed of POMs immobilized on functionalized Merrifield resin (MR) were synthesized, characterized and tested as catalysts for the oxidation of two natural terpenes, β-myrcene and β-caryophyllene, using H2O2 and TBHP as green oxidants. The ionic immobilization enabled easy catalyst recovery and reuse. The results showed high conversion and selectivity, with some catalysts maintaining their efficiency for at least three runs without leaching. The catalytic performances of both homogeneous and heterogeneous systems, along with the necessary characterizations, are discussed.